Pentingnya Perencanaan Jaringan Telekomunikasi - Achmad Dhyta Maulana; Ismah Nurul Syabani; Agung Rizky Jamas; Didik Aribowo (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
Telecommunications network planning is a crucial step in building an efficient and reliable communications infrastructure. In an era where connectivity is the backbone for various human activities, both on an individual and business scale, the importance of telecommunications network planning becomes increasingly apparent. In this abstract, we explain why telecommunications network planning is so important. First, careful planning ensures efficient use of resources, from frequency spectrum to hardware. Second, good planning can anticipate demand growth, ensuring that the network can grow in line with needs without sacrificing service quality. Furthermore, careful planning also considers security, privacy and reliability factors, which are crucial in a telecommunications environment that is constantly changing and vulnerable to threats. Thus, this abstract highlights the importance of telecommunications network planning in facing the challenges and opportunities in an increasingly connected world. With proper planning, telecommunications networks can become a strong backbone for social, economic and technological development.